2019
DOI: 10.1029/2018jd029680
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the Transpiration Fraction and Its Controls Across Typical Ecosystems Within the Heihe River Basin

Abstract: Understanding the seasonality of the transpiration fraction (T/ET) of total terrestrial evapotranspiration (ET) is vital for coupling ecological and hydrological systems and quantifying the heterogeneity among various ecosystems. In this study, a two‐source model was used to estimate T/ET in five ecosystems over the Heihe River Basin. In situ measurements of daily energy flux, sap flow, and surface soil temperature were compared with model outputs for 2014 and 2015. Agreement between model predictions and obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…In the upper reaches, ET 0 is approximately 2 mm d − 1 ; in the middle reaches, ET 0 reaches up to approximately 4 mm d − 1 ; in the lower reaches, ET 0 reaches as high as approximately 8 mm d − 1 . Such a spatial pattern matches the spatial variabilities in temperature and surface net radiation, both of which increase from the upper reaches to the lower reaches (Tong et al, ).…”
Section: Resultssupporting
confidence: 68%
“…In the upper reaches, ET 0 is approximately 2 mm d − 1 ; in the middle reaches, ET 0 reaches up to approximately 4 mm d − 1 ; in the lower reaches, ET 0 reaches as high as approximately 8 mm d − 1 . Such a spatial pattern matches the spatial variabilities in temperature and surface net radiation, both of which increase from the upper reaches to the lower reaches (Tong et al, ).…”
Section: Resultssupporting
confidence: 68%
“…Originally, the SPAC model were used to simulate the actual evapotranspiration (ET a ) and partition ET a into transpiration (T) and evaporation (E). The existing SPAC model achieved good performance in partitioning ET in the humid grasslands of Japan [28], arid and semiarid grassland in Inner Mongolia [21], the typical ecosystem of the Heihe River Basin [25], and Alpine Meadow in Tibetan Plateau [29]. Therefore, we used the main equations of the SPAC model [28] and applied it on the reference land surface in this study.…”
Section: An Updated Reference-spac (R-spac) Model For Etmentioning
confidence: 99%
“…Many multi-source models have been developed to understand energy partitioning between sources and the routing of sensible and latent heat [7,[18][19][20][21]. Two-source models have been shown to be capable of reasonably estimating ET and its components under different climate and vegetation conditions [22][23][24][25]. The FAO PM and updated Shuttle Worth-Wallace dualsource models [18] have been shown to be capable of estimating ET 0 and its components.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that forests had the highest T rate (656 mm/year), followed by rice-wheat rotation field (460 mm/year) and dry land (190 mm/year) ( Figure 8). T was sensitive to changes in plant types and temporal vegetation dynamics [21]. Urbanization may result in the expansion of impervious surfaces with no vegetation, resulting in reduction of T and ET.…”
Section: Implications Of Et Reduction To Regional Ecosystem Productivmentioning
confidence: 99%